Economic development and the environment - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Development research; the environmental challenge edited by James T Winpenny 228pp 1990 UKL9.95 ISBN 0 85003 141 9 published by Overseas Development Institute Regent's College Inner Circle, Regent's Park London NW1 4NS UK